Factors associated with malaria in pregnancy among women attending ANC clinics in selected districts of the Ashanti Region, Ghana - Emmanuel Abu Bonsra; Petra Amankwah Osei; Emmanuel Adjei Kyeremeh; Stephen Adama; Akua Grace Sekyi; Elsie Fafa King (Malaria Journal)
Abstract Background Malaria is a disease deeply rooted in poverty. Malaria in pregnant women leads to severe complications, including low birth weight and neonatal mortality, which can adversely affect both mother and child. This study aimed to identify the factors associated with malaria in pregnancy among women attending antenatal care (ANC) clinics in three districts of the Ashanti Region, Ghana. Methods A cross-sectional study was conducted among 1215 pregnant women selected through multi-stage sampling. Data were collected using structured questionnaires and analysed using descriptive and inferential statistics, including regression analysis. Results The self-reported prevalence of at least one episode of malaria was 76.7% (95% CI [74.1–79.3%]). Age, education, marital status, income, and religion were significantly associated with the prevalence of malaria among pregnant women, with a p-value < 0.001. Pregnant women aged 17–25 years were 10.26 times more likely to have malaria compared to other age groups (aOR = 10.26, 95% CI [4.52–11.05], p = 0.000). Women with no formal education had higher odds of malaria, being 15.10 times more likely to have malaria compared to those with tertiary education (aOR = 15.10, 95% CI [7.32–16.78], p = 0.002). Women not using insecticide-treated bed nets (ITNs) were 20 times more likely to have malaria compared to those who used ITNs (aOR = 20.0, 95% CI [7.04–21.03], p = 0.000). Conclusion Age, education, marital status, income, religion and insecticide-treated bed net (ITN) use significantly influence malaria prevalence in pregnancy. To achieve SDG 3 (Good Health and Well-being), particularly Target 3.1 (reducing maternal mortality) and Target 3.3 (ending malaria), the Ghana Health Service and Ministry of Health should prioritize expanding ITN distribution, educational campaigns, and targeted support for vulnerable groups to reduce malaria prevalence during pregnancy and improve maternal health outcomes.